2019
DOI: 10.31018/jans.v11i1.1964
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and mapping of seasonal vegetation trend in Tamil Nadu using NDVI and NDWI imagery

Abstract: In order to monitor vegetation growth and development over the districts and land covers of Tamil Nadu, India during the crop growing season viz., Khairf and Rabi of 2017, Moderate Resolution Imaging Spectroradiometer (MODIS) derived surface reflectance product (MOD09A1) which is available at 500 m resolution and 8-day temporal period was used to derive a time series based Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) for monitoring and mapping terrestrial vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Specifically, the minimum of NDWI2 (10 th NDWI2 ) and its temporal diversity (Q NDWI2 ) assumed particularly high values and emerged as the most important variables in the first RF cycle. As previously observed, the spectral responses of water and dryland are very different [94,95]. Such differences clearly emerged at coarser classification levels on the transition area we analyzed here.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, the minimum of NDWI2 (10 th NDWI2 ) and its temporal diversity (Q NDWI2 ) assumed particularly high values and emerged as the most important variables in the first RF cycle. As previously observed, the spectral responses of water and dryland are very different [94,95]. Such differences clearly emerged at coarser classification levels on the transition area we analyzed here.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the implemented RF classification organized in sequential cycles ensured accurate and ecologically coherent results. For instance, water presence and seasonality evidenced by the yearly behavior of NDWI2 were important variables in the first cycle of classification implemented on overall coastal area extent, which confirmed its potential for discriminating water from emerged areas [94,95] and suggested its role when mapping transition systems between terrestrial and marine realms. Similarly, our results confirmed that biomass and bare soil indexes and their temporal variability are important variables for mapping terrestrial cover classes [16,28,92,101].…”
Section: Discussionmentioning
confidence: 67%
“…In particular, NDVI [109] is considered the most popular vegetation index in crop monitoring and classification studies [110], being indicative of vegetation's status and photosynthetic activity [111]. NDWI proposed by Gao (1996) [112], is an effective indicator of vegetation's water content [113]. PSRI, defined by Merzlyak (1999) [114] exhibits great sensitivity in the aging stage of plant development.…”
Section: Sentinel-2 Datamentioning
confidence: 99%